2014
DOI: 10.1007/s12046-014-0287-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of experimental breakthrough curves using multiprocess non-equilibrium model for reactive solute transport in stratified porous media

Abstract: In this paper, we have studied the behaviour of reactive solute transport through stratified porous medium under the influence of multi-process nonequilibrium transport model. Various experiments were carried out in the laboratory and the experimental breakthrough curves were observed at spatially placed sampling points for stratified porous medium. Batch sorption studies were also performed to estimate the sorption parameters of the material used in stratified aquifer system. The effects of distance dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 36 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…A skewed shape of experimental and simulated results has been obtained as shown in figures 3, 4, 5, 6, 7 and 8, which is a clear demonstration that the system is under the strong influence of physical nonequilibrium. In the experimental set-up of Swami et al [24], the width of the immobile region is large and that is the reason behind the long tails with a high concentration at the concluding part of the experiments. MIM with time-dependent dispersion has demonstrated capabilities to simulate such complex scenario in pre-asymptotic regime.…”
Section: Simulation Of Experimental Data Of Chloride Transport Througmentioning
confidence: 99%
See 1 more Smart Citation
“…A skewed shape of experimental and simulated results has been obtained as shown in figures 3, 4, 5, 6, 7 and 8, which is a clear demonstration that the system is under the strong influence of physical nonequilibrium. In the experimental set-up of Swami et al [24], the width of the immobile region is large and that is the reason behind the long tails with a high concentration at the concluding part of the experiments. MIM with time-dependent dispersion has demonstrated capabilities to simulate such complex scenario in pre-asymptotic regime.…”
Section: Simulation Of Experimental Data Of Chloride Transport Througmentioning
confidence: 99%
“…It has been observed that the mass transfer coefficient contributes in early arrival and long tailing of BTC apart from retardation factor and dispersion coefficient [16]. In addition to this, the most challenging aspect of studying solute transport through heterogeneous porous media is ever-growing scale effect with space or time on the estimation of dispersion coefficient [17][18][19] since constant dispersion coefficient is a lumped parameter and unable to capture the broad spectrum of time scale BTCs through a heterogeneous porous medium [20][21][22][23][24]. To incorporate the scale effects, time-dependent and scale (distance)-dependent dispersion models in pre-asymptotic regime have been developed over the past decade [8,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Ku mar, et al and the respective initial and boundary conditions Eqs. (18)(19)(20) may be written in terms of ( , ) K Z t , as follows 00 00 ( , ) exp 2 22), i.e., to reduce it into an ordinary differential equation of second order, let us multiply its both sides by exp( ) pt  and integrate it between the limit 0 t  and t , i.e., applying Laplace transformation of parameter p on equation (22), we get 2 0 2 00…”
Section: Uniform Input Point Source Of Pulse Type Conditionmentioning
confidence: 99%
“…The recharge conditions are decreasing due to deforestation and concrete structure build up in large area of urbanization [4] .Climate change also has significant impacts on ground water [5]. Contamination due to land fill and chemical waste from industry are equally responsible for degradation of quality ground water [6][7][8]. Unplanned settlement, bored well and deep well constructions are causing to disturbing the water balance condition.…”
Section: Introductionmentioning
confidence: 99%